The Influence of the Inheritance and Development of Xingyiquan from the Late Qing Dynasty to the Republic of China on Relieving People’s Mental Anxiety about Health - Chunyang Guo, Zhiguo Zhang, Xiaodong Wang (Forest Chemicals Review)
There is a close relationship between the form and content of physical culture of each nation and the collective cultural therapy of each nation. Martial arts, as the principal representative of traditional body culture of the Chinese nation, can reflect the relationship of Chinese physical culture and the collective cultural therapy in a large extent. This paper uses a variety of methods, such as Document Method and Logical Analysis, to study the inheriting and developing history of Xingyi quan in the Late Qing Dynasty and the Republic of China, and to discuss the changes of Xingyi quan in the way of inheritance, connection focus, connection influence and so on. Thus to explore the national culture psychological inprint of Chinese martial arts boxing. During the period of the republic of China in late Qing dynasty, Xingyi quan disciples followed the trend of the development of The Times, instead of spreading Xingyi quan through blood relationship and geographical relationship, they turned to clubs, armies, schools, etc., and increased social visibility and influence through these ways. After Central Martial Arts Academy is built, Xingyi quan, as a combination of coaching and fighting idel martial art, steped into the arena with the essence of actual combat, and became a successful model of traditional martial arts inheritance and development under the historical background of Martial arts modernazation transformation. During the period of the republic of China in late Qing dynasty, Xingyi quan followed the trend of The Times, changed the inheritance methods and original inheritance focus, and increased the spread influence. Although once appeared the trend of “performism” in the process of the inheritance of Xingyi quan, however, look at the long-term trend, Xingyi quan has been following the rule of combining coaching and practice, and had extremely high ability of abilities and actual attack, and reflect the practical features emphasized and outstanding in the Chinese traditional cultural psychology. History can be found, Xingyi quan athletic performance is a "real" to the traditional martial arts class of historical nihilism tone refutation, and reflects the current development of traditional martial arts light along the lines of: coaching combined with practice. History is any guide, inheritance and development of traditional martial arts to combining history and reality, the essential function and extending function. In the face of the question of “perform or practice”, we should find the root of this problem, overcome in the future inheritance, and let the traditional martial arts development back on track, make martial arts "shape" and "spirit" synchronous transmission.